The Relationships between GDP growth, Energy Consumption, Renewable Energy Production and CO2 Emissions in European Transition Economies - Muço, Klodian; Valentini, Enzo; Lucarelli, Stefano (International Journal of Energy Economics and Policy, 2021)
The objective of the analysis is to study the relationships between GDP, energy consumption, renewable energy production, and CO2 emissions in some European transition economies in the period 1990-2018. We use the growth rates of per capita values, in a panel VAR approach where all variables are typically treated as endogenous, allowing some inference on the causality of the relationships. The decision to focus on European transition countries is motivated by the fact that a significant part of the future of the green economy in Europe depends on the environmental and energy policies that will be implemented by these countries. In the transition economies (and years) included in the analysis, our findings suggest that investing in energy efficiency is good for the competitiveness of economies (in terms of effects on GDP growth) and is good for the environment (in terms of diminishing CO2 emissions). Finally, an increasing production of renewable energies reduces CO2 emissions. Keywords: Energy consumption; Economic growth; Renewable energy; CO2 emissions; Transition countries. JEL Classifications: O44, Q43 DOI: https://doi.org/10.32479/ijeep.11275